Gender Bias and Religious Conservatism in Indonesia: An Analysis of the Shuniyya Ruhama Case on Social Media - Fitri, Susanti Ainul; Marzal, Novrizon; Mukhroman, Iman; Effendi, Dudy Imanuddin; Solahudin, Dindin (Jurnal Iman dan Spiritualitas, 2025)
This study analyzes how gender bias and religious conservatism are reproduced through social media in Indonesia, using the viral case study of Shuniyya Ruhama, a female religious teacher who was attacked online for expressing religious views that were considered incompatible with conservative interpretations. The objective of this study is to uncover the dynamics of the representation of female religious authority and resistance to it in the digital space. The methodology employed is Norman Fairclough's Critical Discourse Analysis (CDA), utilizing data from the platforms X (Twitter), Threads, and TikTok, using a purposive sampling technique. Findings indicate that women who deliver religious sermons often face delegitimization through misogynistic religious narratives that reinforce the hegemony of religious patriarchy. Symbolic representations in the form of labeling, hate speech, and the removal of women’s religious authority status reveal unequal power dynamics. On the other hand, counter-narratives emerge from progressive communities advocating for equality in religious interpretation and women’s religious authority. This study shows that social media is not neutral, but rather an ideological arena where conservative discourse is both perpetuated and challenged. The implications of this study include the need for a reformulation of gender-fair media representation and support for digital public spaces that are inclusive of women in religious discourse.